Identification of the Puting Beliung Event by Utilizing the Interpretations of Radar Products and Himawari-8 Weather Satellite (Case Study Puting Beliung Incident, November 22, 2018 in Jakarta) - Iga Rusmala; R. Zikri; R. N. Rahman; M. I. R. Ansori; I. R. Nugraheni; A. Ali (Pusat Penelitian dan Pengembangan BMKG, 2022)
Indonesia was shocked again by a Puting beliung or tornado-like incident on November 22, 2018, in the Jakarta area. This incident caused many losses. In this regard, a study was conducted to observe the reflectivity products to identifiy the hook echo or bow echo patterns, and the velocity products for mesocyclone patterns as the characteristic of the Puting Beliung used radar product. The study required the Cengkareng C-Band raw data radar that was processed to produce CMAX, VCUT, and CAPPI (V) at 0.5 km, 1.0 km, and 1.5 km elevations overlay by HWIND. The CMAX and VCUT radar products are used to identify the cloud structure that caused Puting Beliung, by observed the highest reflectivity of the Puting Beliung-producing clouds. Then the CAPPI product overlay by HWIND is used to identify the movement of the wind which is suspected to be the beginning of the formation of a Puting Beliung at that location which is characterized by the presence of a mesocyclone pattern in the form of wind components and radial velocity. It was suspected that there was a wind rotating in the Central Jakarta area which indicated a Puting Beliung in the area. The analysis of this radar interpretation was then validated using satellite imagery to detect the cumulonimbus clouds forming the Puting Beliung. From this research, it is known that the Puting Beliung occurred around 08.12 UTC. The growth of cyclone-producing clouds occurred rapidly with a reflectivity value between 35 - 45 dBZ and wind speed up to 35 knots. Analysis of satellite imagery showed a significant decrease in cloud peak temperature so that the formation of convective clouds in the form of Cumulonimbus clouds indicates the phenomenon of the Puting Beliung. However, in this case study the Puting Beliung phenomenon is indicated as seen from the mesocyclone pattern of the rotating radial velocity component, and not from the hook echo or bow echo pattern.